Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1111/j.1151-2916.1990.tb06582.x
|View full text |Cite
|
Sign up to set email alerts
|

29Si Magic‐Angle‐Spinning Nuclear Magnetic Resonance Study of Hydrated Cement Paste and Mortar

Abstract: This paper presents 29Si magic-angle-spinning nuclear magnetic resonance measurements that trace the cement hydration process in cement paste and mortar specimens made from ordinary portland cement, type I. These specimens were moist-cured for 3, 7, 14, and 28/31 d at temperatures ranging from 21" to 80°C. Compressive strength for all tested specimens was also determined. The results show that the degree of hydration (Q' -k Q') and the compressive strength increase with curing times and temperatures. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…It also supported more hydration as the Q 0 peak belonged to the C 3 S and C 2 S. The intensity of the Q 1 peak decreased and the intensity of the Q 2 peak increased, resulting in an increase in the value of MCL. Through this, the activation of a cement hydration reaction could be seen as making the average length of the silicate chain longer [42][43][44].…”
Section: Cement Hydration Under Low Water Amount and High Temperaturementioning
confidence: 99%
“…It also supported more hydration as the Q 0 peak belonged to the C 3 S and C 2 S. The intensity of the Q 1 peak decreased and the intensity of the Q 2 peak increased, resulting in an increase in the value of MCL. Through this, the activation of a cement hydration reaction could be seen as making the average length of the silicate chain longer [42][43][44].…”
Section: Cement Hydration Under Low Water Amount and High Temperaturementioning
confidence: 99%
“…Most studies on the effect of temperature analyze its impact on the mechanical properties of cement. 14,15 Other studies explore its effect on C-S-H gel composition based on the Ca/Si ratios observed in TEM/EDX or SEM/EDX analyses of cement paste or mortar. 16,17 Very few studies have addressed the degree of polymerization deduced from the Q 2 / Q 1 ratio indirectly obtained with 29 Si MAS NMR.…”
Section: Introductionmentioning
confidence: 99%
“…In QXRD, the cement hydration degree is calculated based on the low-content crystal phases, so accuracy is limited in these circumstances [ 2 ]. In MAS NMR, overlapping of the peaks of calcium silicate hydrate gel (C-S-H) and SCMs causes deconvolution problems; furthermore, the ferrum in cement and FA leads to line broadening, which generally hinders the use of MAS NMR [ 32 , 33 ]. The application of the non-evaporable water method depends on assumptions about a specific water content bonded by the cement clinker, which is thought to be about 0.23.…”
Section: Methodsmentioning
confidence: 99%